2007
DOI: 10.1143/jpsj.76.023703
|View full text |Cite
|
Sign up to set email alerts
|

Universal Scaling in the Dynamical Conductivity of Heavy Fermion Ce and Yb Compounds

Abstract: Dynamical conductivity spectra [σ(ω)] have been measured for many heavy-fermion (HF) Ce and Yb compounds. A characteristic excitation peak has been observed in the infrared region of σ(ω) for all the compounds, and has been analyzed in terms of a simple model based on conduction (c)-f electron hybridized band. A universal scaling is found between the observed peak energies and the estimated c-f hybridization strengths of these HF compounds. This scaling demonstrates that the model of c-f hybridized band can ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 49 publications
4
72
0
Order By: Relevance
“…For T ≤ T 0 , the zero-field anomalies in χ(T ) and C V (T ) yield an enhanced effective mass 27 of the order of 1/T 0 and the neutron scattering data 29,30 show a narrow peak at about 30 meV, which is due to a hybridization gap. However, if we plot the low-temperature transport coefficients on a reduced temperature scale T/T K they appear to be strongly enhanced with respect to the predictions of the single impurity Anderson model with Kondo scale T K ≃ 500 K. Neither the A coefficient of the resistivity nor the slope of the thermopower can be explained by the single impurity c calculations that would capture the main features of the high-temperature data and give T K ≃ 500 K. Optical conductivity at 7 K shows a narrow Drude-like response that is often found in heavy fermion systems 32,33 and another mid-infrared peak (MIR) that can be associated with the hybridization gap. The optical spectra do not change appreciably for 7 K ≤T≤ 40 K, as expected of a system with the characteristic energy scale T 0 ≃ 50 K. However, the Drude peak broadens and the MIR peak vanishes at higher temperatures.…”
Section: The T0 ≪ Tk Casementioning
confidence: 84%
“…For T ≤ T 0 , the zero-field anomalies in χ(T ) and C V (T ) yield an enhanced effective mass 27 of the order of 1/T 0 and the neutron scattering data 29,30 show a narrow peak at about 30 meV, which is due to a hybridization gap. However, if we plot the low-temperature transport coefficients on a reduced temperature scale T/T K they appear to be strongly enhanced with respect to the predictions of the single impurity Anderson model with Kondo scale T K ≃ 500 K. Neither the A coefficient of the resistivity nor the slope of the thermopower can be explained by the single impurity c calculations that would capture the main features of the high-temperature data and give T K ≃ 500 K. Optical conductivity at 7 K shows a narrow Drude-like response that is often found in heavy fermion systems 32,33 and another mid-infrared peak (MIR) that can be associated with the hybridization gap. The optical spectra do not change appreciably for 7 K ≤T≤ 40 K, as expected of a system with the characteristic energy scale T 0 ≃ 50 K. However, the Drude peak broadens and the MIR peak vanishes at higher temperatures.…”
Section: The T0 ≪ Tk Casementioning
confidence: 84%
“…They suggested that the bandwidth W of a Ce (Yb) compound could be regarded as inversely proportional to specific heat coefficient γ of the non-magnetic, isostructural La (Lu) compound (denoted as γ 0 ). T K is expressed in terms of the electronic specific heat coefficient γ as 28,48…”
Section: Universal Scaling In Ce-and Yb-based Compoundsmentioning
confidence: 99%
“…The hybridization gap in the infrared is another well-studied characteristic of heavy-fermion optics. 12,13 It is usually attributed to excitations over the gap in the density of states that develops due to the hybridization, 14 but there are also recent calculations that describe such a gap structure in the conductivity as a band-structure effect. 15,16 In the present study we concentrate on frequencies that are much lower than those typically assumed for the hybridization gap.…”
Section: Introductionmentioning
confidence: 99%